Inhibition of PI3Kγ by AS605240 Protects tMCAO Mice by Attenuating Pro-Inflammatory Signaling and Cytokine Release in Reactive Astrocytes. (1st September 2019) - Shang, Sen; Liu, Lin; Wu, Xingjuan; Fan, Fan; Hu, Erling; Wang, Leilei; Ding, Yan; Zhang, Yali; Lu, Xiaoyun
Abstract: The intense and prolonged inflammatory response after ischemic stroke significantly contributes to the secondary neural injury. PI3Kγ, which is involved in the regulation of vascular permeability, chemotactic leukocyte migration and microglia activation, is a key target for intervention in the inflammatory response. In this study, we identified the protective effect of the PI3Kγ inhibitor AS605240 against stroke-related injury in the mouse model of transient intraluminal middle cerebral artery occlusion (tMCAO). The results showed that administration of AS605240 could improve the neurological function score, reduce the infarct size and decrease astrocyte activation in the tMCAO mice after injury. The inhibitory effect of AS605240 on microglia activation is relatively clear. Therefore, in this study, the effects of AS605240 on astrocytes were studied in cell cultures. IL-6 and its soluble receptor were used to construct the astrocyte activation model. AS605240 treatment significantly reduced the astrocyte activation markers and the morphological changes of cells. We also identified 13 inflammatory factors whose expression was significantly upregulated by IL-6/sIL-6R and significantly inhibited by AS605240 at the protein level, and seven of those factors were verified at the mRNA level. These results indicated that specific inhibition of PI3Kγ could reduce astrocyte activation induced by inflammation, which might aid the repair and remodeling of neurons in the later stage after ischemic stroke. Highlights: AS605240 improved neurological function score, reduced infarct size and decreased astrocytes activation in tMCAO mice. AS605240 inhibited ischemia-induced and IL-6/sIL6R induced activation of astrocytes. AS605240 reduced IL-6/sIL6R induced inflammatory factors release in primary astrocyte. PI3Kgamma regulated IL-6/sIL6R induced phosphorylation of AKT and STAT3 and activation of NF-κB.